The Organization of International Trade - Dominik Boddin; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper discusses how international trade is organized from export to trans-boundary transport to import. All evidence suggests that the transport sector is independent, may exercise market power and features strong economies of scale. We develop a model of a transport industry that operates under imperfect competition and economies of scale and two generic trade models in which export and import activities are either organized at arm's length or in a vertical partnership. Using a large dataset of maritime transport costs, tariffs and export prices, we test the model predictions and find that economies of scale beat market power: a decline in the tariff implies a decline in freight rates. Furthermore, our results are consistent only with international trade being organized in vertical partnerships because a tariff increase does not lead to a decrease in export prices.
Keywords: F12; F14; R40; 330; trade costs; transport costs; export prices; vertical integration